Fernando Pessoa’s Fausto and the concept of Subjective Tragedy - Xavier, Rodrigo Alexandre (Acta Scientiarum. Language and Culture, 2016)
This paper intends to show, in an embryonic format, how Fernando Pessoa embodied the subjective process, presented in all his work through a heteronimic construction, in his writing project of Portuguese Faust. Consistent with the idea of Static Drama, Pessoa’s Fausto sights the construction of an animistic and apathetic tragedy, supported on a discursive monologism and the tragic conception of existence.